2022
DOI: 10.3389/fneur.2022.912039
|View full text |Cite
|
Sign up to set email alerts
|

Chromobox 7/8 serve as independent indicators for glioblastoma via promoting proliferation and invasion of glioma cells

Abstract: BackgroundThe chromobox family, a critical component of epigenetic regulators, participates in the tumorigenesis and progression of many malignancies. However, the roles of the CBX family members (CBXs) in glioblastoma (GBM) remain unclear.MethodsThe mRNA expression of CBXs was analyzed in tissues and cell lines by Oncomine and Cancer Cell Line Encyclopedia (CCLE). The differential expression of CBXs at the mRNA level was explored in The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…As a tumor suppressor, CBX7 is expressed at low levels in most tumors, such as glioma, HNSCC (71), EC (87,88), GC (93)(94)(95)(96)(97)(98), PAAD (109), CRC (103,104), clear cell renal cell carcinoma (ccRCC) (110), ovarian cancer (OC) (111), cervical carcinoma (CCA) (112) and skin cutaneous melanoma (SKCM) (113), while all CBX members, including CBX7 in hepatocellular carcinoma (HCC) (11,(114)(115)(116)(117)(118)(119)(120)(121)(122), have been proven to be tumor-promoting factors. The expression of CBX6 is different in different cancer types, with low expression in glioma (67,68), BC (77,80), CRC (103,104), ccRCC (110) and OC (111), but high expression in HNSCC (71), sarcoma (106) and SKCM (113). The results of studies on the expression of CBX in the same type of cancer are not completely consistent.…”
Section: Expression Of Cbxs In Cancers and The Relationship Between C...mentioning
confidence: 97%
See 2 more Smart Citations
“…As a tumor suppressor, CBX7 is expressed at low levels in most tumors, such as glioma, HNSCC (71), EC (87,88), GC (93)(94)(95)(96)(97)(98), PAAD (109), CRC (103,104), clear cell renal cell carcinoma (ccRCC) (110), ovarian cancer (OC) (111), cervical carcinoma (CCA) (112) and skin cutaneous melanoma (SKCM) (113), while all CBX members, including CBX7 in hepatocellular carcinoma (HCC) (11,(114)(115)(116)(117)(118)(119)(120)(121)(122), have been proven to be tumor-promoting factors. The expression of CBX6 is different in different cancer types, with low expression in glioma (67,68), BC (77,80), CRC (103,104), ccRCC (110) and OC (111), but high expression in HNSCC (71), sarcoma (106) and SKCM (113). The results of studies on the expression of CBX in the same type of cancer are not completely consistent.…”
Section: Expression Of Cbxs In Cancers and The Relationship Between C...mentioning
confidence: 97%
“…High expression of CBX2/3/8 in glioma (67,69), CBX2 in EC (89) and CBX1 in HCC (115) was indicated to lead to a high probability of tumor recurrence. In terms of other cancer characteristics, CBX2/6/7 is closely related to the isocitrate dehydrogenase mutation in glioma (68), CBX2 is related to a human epidermal growth factor receptor (EGFR)2-positive status of BC ( 74) and CBX3 is related to EGFR mutation in NSCLC (82). CBX1, CBX3 and CBX7 are also associated with vascular invasion in HCC (115), HNSCC (71) and CCA (112), respectively.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed the distinct Integrative Analysis of Genetic and Epigenetic Alterations in the CBX7 Gene Reveals Oncol Insights.2023;2:691 functions among CBX family members in cancer. For example, CBX3 was found to be upregulated, whereas CBX7 was downregulated in many types of human cancer [14][15][16][17][18][19][20][21][22]. Some studies have shown that CBX3 transcriptionally suppresses the p21 gene to promote cell proliferation [23][24][25], while CBX7 transcriptionally suppresses CCNE1 expression to inhibit cell proliferation [26].…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that some CBX genes function as oncogenes and others act as tumor suppressor genes. Moreover, the expression of many CBX genes has a prognostic impact on human cancer [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%